2012
DOI: 10.1155/2012/715942
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Yoga for Pregnant Women: Current Status and Future Directions

Abstract: Objectives. Yoga is used for a variety of immunological, neuromuscular, psychological, and pain conditions. Recent studies indicate that it may be effective in improving pregnancy, labour, and birth outcomes. The purpose of this paper is to evaluate the existing literature on yoga for pregnancy. Methods. Six databases were searched using the terms “yoga AND pregnancy” and “yoga AND [post-natal OR post-partum]”. Trials were considered if they were controlled and evaluated a yoga intervention. All studies were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 38 publications
5
78
0
15
Order By: Relevance
“…Nonpharmacological interventions may offer benefit as many pregnant women report preference for such options [25,43]. Complementary and integrative practices, such as yoga, are gaining acceptance as viable treatment options for a range of physical and mental health problems [5,6,13,34,45,48]. A systematic review of 12 randomized controlled trials of yoga as an intervention for depression among a general population of adults found yoga to be an effective intervention in the short-term treatment of depression [11].…”
Section: Yoga As An Intervention For Antenatal Depression and Anxietymentioning
confidence: 99%
“…Nonpharmacological interventions may offer benefit as many pregnant women report preference for such options [25,43]. Complementary and integrative practices, such as yoga, are gaining acceptance as viable treatment options for a range of physical and mental health problems [5,6,13,34,45,48]. A systematic review of 12 randomized controlled trials of yoga as an intervention for depression among a general population of adults found yoga to be an effective intervention in the short-term treatment of depression [11].…”
Section: Yoga As An Intervention For Antenatal Depression and Anxietymentioning
confidence: 99%
“…The purpose of yoga is to use body mechanics, respiration techniques, control of the mind, meditation and thought application and creating balance in the emotional, mental, physical and spiritual levels [26]. In this study, it was seen that the yoga application had a statistically positive effect on posture.…”
Section: Discussionmentioning
confidence: 60%
“…Gebenin stresini, öfkesini azaltır daha sakin ve daha kontrollü daha huzurlu olmasını sağlar. Doğum sonrasında da annenin bebeği kabullenme sürecini hızlandırır (Curtis, Weinrib and Katz 2012;Wren, Wright, Carson and Keefe 2011).…”
Section: Gġrġġunclassified